Early deficits in olfaction are associated with structural and molecular alterations in the olfactory system of a Huntington disease mouse model. (21st May 2020) - Laroche, M; Lessard-Beaudoin, M; Garcia-Miralles, M; Kreidy, C; Peachey, E; Leavitt, B R; Pouladi, M A; Graham, R K
Abstract: Olfactory dysfunction and altered neurogenesis are observed in several neurodegenerative disorders including Huntington disease (HD). These deficits occur early and correlate with a decline in global cognitive performance, depression and structural abnormalities of the olfactory system including the olfactory epithelium, bulb and cortices. However, the role of olfactory system dysfunction in the pathogenesis of HD remains poorly understood and the mechanisms underlying this dysfunction are unknown. We show that deficits in odour identification, discrimination and memory occur in HD individuals. Assessment of the olfactory system in an HD murine model demonstrates structural abnormalities in the olfactory bulb (OB) and piriform cortex, the primary cortical recipient of OB projections. Furthermore, a decrease in piriform neuronal counts and altered expression levels of neuronal nuclei and tyrosine hydroxylase in the OB are observed in the YAC128 HD model. Similar to the human HD condition, olfactory dysfunction is an early phenotype in the YAC128 mice and concurrent with caspase activation in the murine HD OB. These data provide a link between the structural olfactory brain region atrophy and olfactory dysfunction in HD and suggest that cell proliferation and cell death pathways are compromised and may contribute to the olfactory deficits in HD.